A Case Report of Advanced Male Breast Cancer in A 70 Years Old Patient - Ghosh, Ashim K; Hosen, MM Arif; Khatun, Julekha; Akhter, Hasnina; Shimu, F Farjana; Sarkar, SM (TAJ: Journal of Teachers Association, 2018)
Male breast cancer is rare. It accounts for 0.2% of all cancers and about 1% of all breast cancer. Because of the rarity of the disease and the low index of suspension, diagnosis is delayed in a significant fraction of patients. The objective of this article is to increase the medical community's awareness of the disease in this setting and thus favorably change its natural history by earlier diagnosis. The present study reported the case of a 70 year old man who was diagnosed with an advanced infiltrating ductal carcinoma. TAJ 2013; 26: 103-105